2017
DOI: 10.1038/s41598-017-02101-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of trace element magnesium significantly improving the cognition and locomotion in hepatic encephalopathy rats

Abstract: The therapeutic effects of iron, zinc and magnesium trace elements, as well as rifaximin were investigated and compared in HE rats. In this study, HE rats were treated with either ferrous sulfate (HE-Fe, 30 mg/kg/day), zinc sulfate (HE-Zn, 30 mg/kg/day), magnesium sulfate (HE-Mg, 50 mg/kg/day) or rifaximin (HE-Rf, 50 mg/kg/day), which was mixed with water and administered orally for 61 days. The Morris water maze (MWM) and open-field tests were used to evaluate cognitive and locomotor function. The blood ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…As we concluded above, the change in ammonia level did not affect brain Mn content, while the change of brain Mn content affected the ammonia level. By further considering previous studies (17,23), which revealed that MgSO 4 could significantly increase fecal Mn excretion to reduce brain Mn content, we speculated that MgSO 4 decreased the blood ammonia level and brain GLN content by increasing the amount of fecal Mn excretion to decrease the brain Mn content and by regulating brain GS activity.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…As we concluded above, the change in ammonia level did not affect brain Mn content, while the change of brain Mn content affected the ammonia level. By further considering previous studies (17,23), which revealed that MgSO 4 could significantly increase fecal Mn excretion to reduce brain Mn content, we speculated that MgSO 4 decreased the blood ammonia level and brain GLN content by increasing the amount of fecal Mn excretion to decrease the brain Mn content and by regulating brain GS activity.…”
Section: Discussionmentioning
confidence: 66%
“…The latency and the total time of the NBT were recorded. Therefore, MWM, Y maze, and NBT were performed according to the previous protocols (17)(18)(19)(20).…”
Section: Behavioral Assessment Of Mhe Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of omeprazole was based on an oral human dose of 40 mg normalized to body surface area, and it was smaller than previously reported study [ 17 ]. The doses of magnesium sulfate [ 18 ] and famotidine [ 19 ] have been shown effective modulation of the biological activities. The rats were kept in cabinets controlled for temperature, humidity, and light.…”
Section: Methodsmentioning
confidence: 99%